2011
DOI: 10.1159/000324627
|View full text |Cite
|
Sign up to set email alerts
|

Memory Complaints in Chronic Stroke Patients Are Predicted by Memory Self-Efficacy rather than Memory Capacity

Abstract: Background: Memory self-efficacy (MSE) is the belief about one’s mastery of memory functioning. In healthy elderly, memory complaints are related to MSE rather than to objectively measured memory capacity. MSE has scarcely been studied in patients that suffered a stroke. The aim of this study was twofold: (1) to examine whether memory capacity and MSE can predict the presence of memory complaints in stroke patients, and (2) to study which variables are the best predictors of MSE. Methods: In a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 87 publications
(49 reference statements)
8
37
3
2
Order By: Relevance
“…Whether this is also true for patients who had a stroke is less well established. Aben et al (2011) found a relationship between neuroticism and memory-related SCC, which became non-significant in covariate-adjusted models. An association with extraversion or coping style with post-stroke SCC was not found in that study (Aben et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Whether this is also true for patients who had a stroke is less well established. Aben et al (2011) found a relationship between neuroticism and memory-related SCC, which became non-significant in covariate-adjusted models. An association with extraversion or coping style with post-stroke SCC was not found in that study (Aben et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Multiple studies indicate that psychological factors are related to SCC, particularly poststroke depression (Aben et al, 2011;Duits et al, 2008;Lamb, Anderson, Saling, & Dewey, 2013;Maaijwee et al, 2014;Martin, Dellatolas, Viguier, Willadino-Braga, & Deloche, 2002;Nijsse et al, 2017;Winkens et al, 2009;Xiong et al, 2011). Most studies demonstrated that post-stroke depressive symptoms are associated with more SCC (Aben et al, 2011;Duits et al, 2008;Lamb et al, 2013;Maaijwee et al, 2014;Martin et al, 2002;Nijsse et al, 2017;Winkens et al, 2009;Xiong et al, 2011), although one study did not find such a relationship (Narasimhalu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre los factores que se relacionan con la auto percepción de alteración de la memoria, se puede mencionar a la edad, las comorbilidades cardiovasculares, los síntomas depresivos y el sexo femenino [30][31][32] . Los resultados del presente estudio están acorde con lo mostrado por la literatura previa, donde se identifica estos factores relacionados con una auto-percepción de pérdida de memoria.…”
Section: Factores Asociados a La Auto-percepción De Pérdida De Memoriaunclassified
“…La presencia de síntomas depresivos en las personas genera bradipsiquia y comportamientos relacionados al desgano. Por ello, las actividades cognitivas, como la memoria tienden a disminuir, lo que se evidencia en los resultados de los estudios previos [30][31][32] . Por otro lado, la educación superior condiciona un entrenamiento cognitivo mayor, lo que genera una mayor actividad sináptica.…”
Section: Factores Asociados a La Auto-percepción De Pérdida De Memoriaunclassified